2015
DOI: 10.4142/jvs.2015.16.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pharmacological and genetic inhibition of cyclooxygenase-2: effects on adult neurogenesis in the hippocampal dentate gyrus

Abstract: Inducible cyclooxygenase-2 (COX-2) has received much attention because of its role in neuro-inflammation and synaptic plasticity. Even though COX-2 levels are high in healthy animals, the function of this factor in adult neurogenesis has not been clearly demonstrated. Therefore, we performed the present study to compare the effects of pharmacological and genetic inhibition of COX-2 on adult hippocampal neurogenesis. Physiological saline or the same volume containing celecoxib was administered perorally every d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
5
23
1
Order By: Relevance
“…COX-2 immunoreactivity was identified in the granule cells of the dentate gyrus, and the pyramidal cells of the hippocampal CA2/3 region. This result is consistent with previous studies involving mice and rats (7,9). In humans, significant neuronal COX-2 immunoreactivity has been identified in the CA3 region, subiculum, entorhinal cortex and transentorhinal cortex (17).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…COX-2 immunoreactivity was identified in the granule cells of the dentate gyrus, and the pyramidal cells of the hippocampal CA2/3 region. This result is consistent with previous studies involving mice and rats (7,9). In humans, significant neuronal COX-2 immunoreactivity has been identified in the CA3 region, subiculum, entorhinal cortex and transentorhinal cortex (17).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated that constitutive COX-2 expression is closely associated with neuroblast differentiation in the dentate gyrus (7,9). The present study observed age-associated alterations in constitutive COX-2 expression in the hippocampus.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In certain types of brain injury, COX-2 serves multiple roles in the regulation of adult hippocampal neurogenesis in the dentate gyrus ( 20 22 ). Knockdown of COX-2 significantly reduces the number of proliferating cells and differentiated neuroblasts in the dentate gyrus compared with wild-type littermates ( 21 , 22 ). In a previous study ( 23 ), we demonstrated that the blocking constitutive COX-2 in the hippocampus by celecoxib, a COX-2 inhibitor, significantly decreased cell proliferation and neuroblast differentiation in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 92%
“…Numerous studies have also reported that pro-inflammatory cytokines exert harmful effects on neurogenesis 34 . Upregulation of pro-inflammatory IL-1β, IL-6, and TNF-α triggers additional pathways, such as COX-2 37 , which is also implicated neuro-inflammation and neurogenesis 38 , although COX-2 seems to have an opposite effect compared to pro-inflammatory cytokines. The upregulation of COX-2 observed in our study might represent a feedback mechanism that is invoked to compensate for impaired (e.g.…”
Section: Discussionmentioning
confidence: 99%